Two new species of the Clubiona corticalis-group from Guizhou Province, China (Araneae: Clubionidae) - Zhang, Jianshuang; Yu, Hao; Zhong, Yang (Zootaxa, 2018)
Clubiona Latreille, 1804, the largest genus in family Clubionidae, currently includes 495 species worldwide with 126 species from China (Li & Lin 2016; World Spider Catalog 2018). Due to the high diversity in Clubiona, several subgenera and species-groups have been proposed (Wang et al. 2015). While there is no agreement on the limits of most species-groups of Clubiona (Deeleman-Reinhold 2001), the corticalis-group has been widely considered as putatively monophyletic. The group presents a distinct set of characters (Mikhailov 1995; Deeleman-Reinhold 2001; Liu et al. 2016) and the species composition of the core-group is relatively stable (Mikhailov 1995; Deeleman-Reinhold 2001; Dankittipakul & Singtripop 2008; Wu et al. 2015). At least two generic names are available for the corticalis-group, Atalia Thorell, 1887 and Paraclubiona Lohmander, 1944 (Mikhailov 2012). Spiders of the corticalis-group are well studied in China and several new species have been described in recent years (Yu et al. 2012; Zhu et al. 2012; Wang et al. 2015; Wu et al. 2015; Liu et al. 2016; He et al. 2016). Up to now, the Clubiona corticalis-group has more than 28 Chinese species (Wang et al. 2015; Wu et al. 2015; Liu et al. 2016; He et al. 2016; Yu et al. 2017), making it one of the most well known clubionid groups in China. While examining spiders collected from Guizhou Province, China, we came across some specimens from the Clubiona corticalis-group, which are described here as belonging to two new species.